A study to evaluate patterns of superficial venous reflux in patients with primary chronic venous disease. (August 2015) - Qureshi, Mahim I; Gohel, Manj; Wing, Louise; MacDonald, Andrew; Lim, Chung S; Ellis, Mary; Franklin, Ian J; Davies, Alun H
Objective: This study assessed patterns of superficial reflux in patients with primary chronic venous disease. Methods: Retrospective review of all patient venous duplex ultrasonography reports at one institution between 2000 and 2009. Legs with secondary, deep or no superficial reflux were excluded. Results: In total, 8654 limbs were scanned; 2559 legs from 2053 patients (mean age 52.3 years) were included for analysis. Great saphenous vein reflux predominated (68%), followed by combined great saphenous vein/small saphenous vein reflux (20%) and small saphenous vein reflux (7%). The majority of legs with competent saphenofemoral junction had below-knee great saphenous vein reflux (53%); incompetent saphenofemoral junction was associated with combined above and below-knee great saphenous vein reflux (72%). Isolated small saphenous vein reflux was associated with saphenopopliteal junction incompetence (61%), although the majority of all small saphenous vein reflux limbs had a competent saphenopopliteal junction (57%). Conclusion: Superficial venous reflux does not necessarily originate from a saphenous junction. Large prospective studies with interval duplex ultrasonography are required to unravel the natural history of primary chronic venous disease.